Analisis Peran Case Manager dalam Kendali Mutu dan Kendali Biaya Pelayanan Rawat Inap Bedah di Rumah Sakit Universitas Indonesia Tahun 2022 - Viano, Natasya C; Junadi, Purnawan (UI Scholars Hub, 2025)
Patient Service Management is carried out by the case manager to create quality services with efficient cost. This study aims to evaluate the role of case managers in quality and cost control of surgical inpatients with JKN assurance at the UI Hospital in 2022. This study uses the concept of Donabedian and KARS guidelines. Quality control is seen from Length of Stay (LOS), patient satisfaction, compliance with clinical pathway, compliance with doctor visits, and delays in elective surgery. Cost control is seen from the difference between INA-CBG's claims and hospital bills and cost formulations. Secondary data were collected from medical records and document reviews. The data were processed with Microsoft Excel. The three common procedures were conducted with Focus Group Discussion (FGD) and interviews to find out the role of case managers. It was found that the role of the case manager at UI Hospital had improved compared to 2021. The case manager's performance is good based on the difference in overall surgical patient claims, LOS control, the level of patient satisfaction, the level of compliance with doctor visits, and the level of compliance with the clinical pathway. Only the level of delay in elective surgery at UI Hospital has not reached the target.